2019
DOI: 10.1186/s40168-019-0677-7
|View full text |Cite
|
Sign up to set email alerts
|

Maize synthesized benzoxazinoids affect the host associated microbiome

Abstract: Background: Plants actively shape their associated microbial communities by synthesizing bio-active substances. Plant secondary metabolites are known for their signaling and plant defense functions, yet little is known about their overall effect on the plant microbiome. In this work, we studied the effects of benzoxazinoids (BXs), a group of secondary metabolites present in maize, on the host-associated microbial structure. Using BX knockout mutants and their W22 parental lines, we employed 16S and ITS2 rRNA g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
223
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 232 publications
(246 citation statements)
references
References 97 publications
(121 reference statements)
18
223
5
Order By: Relevance
“…A recent study reported that the molecular functions of the BXDs are diverse beyond their toxicity. It was suggested that the BXDs function in shaping the root microbiome by selectively attracting the plant-beneficial rhizobacterium Pseudomonas putida [90,91], and are also used as iron chelators [92]. Also, it has been estimated that naturally occurring DIMBOA may govern a physical defense mechanism against aphid feeding by the accumulation of callose [93].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that the molecular functions of the BXDs are diverse beyond their toxicity. It was suggested that the BXDs function in shaping the root microbiome by selectively attracting the plant-beneficial rhizobacterium Pseudomonas putida [90,91], and are also used as iron chelators [92]. Also, it has been estimated that naturally occurring DIMBOA may govern a physical defense mechanism against aphid feeding by the accumulation of callose [93].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, this scenario is compatible with a limited number of genes controlling the biosynthesis and rhizodeposition of defensive secondary metabolites which have been implicated in shaping the plant microbiota 44 . Among these compounds, the indol-alkaloids benzoxazinoids recently gained centre-stage as master regulators of the maize-associated microbial communities 4547 . Interestingly, Hordeum vulgare has evolved a distinct indol-alkaloid compound, gramine 48 , which is preferentially accumulated in the tissues of the wild genotypes compared to ‘Elite’ varieites 49 and whose physiological properties are comparable to the ones of benzoxazinoids 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the extrapolation of results obtained in vitro to rhizosphere and in planta conditions is not straightforward. For many compounds, information about their concentrations in roots, and in particular in rhizosphere soil, is sparse, and the concentration in the rhizosphere may easily be 1000 times lower than in the roots (Kudjordjie et al, 2019). We thus emphasize that effects detected at low concentrations, i.e.…”
Section: Application Of Root Metabolites In Nematode Management-challmentioning
confidence: 99%